(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To determine the risk factors associated with preterm neonatal mortality in the pediatric center of Bach Mai Hospital. Subject and methods: A prospective descriptive study was conducted on 324 preterm neonatal admitted to the pediatric center of Bach Mai Hospital. Results: The preterm infant mortality rate was 12.7%. The risk factors, including Maternal illnesses, hypothermia, SpO2< 90%, Apgar score < 5, a patient coming from the countryside, patients who were mechanically ventilated, congenital disabilities and low-birth-weight are risk factors associated with increased preterm neonatal mortality has statistically significant with p≤ 0,05. The profound impact on preterm neonatal mortality was hypothermia, birth defects, One minute Apgar score < 5, patients mechanically ventilated and patients from the countryside. Conclusion: Enhance health care for pregnancy, especially for maternal illnesses and living in countryside. Improving Delivery Room Resuscitation for Infants Affected by maternal conditions.